2023
DOI: 10.3390/pharmacy12010004
|View full text |Cite
|
Sign up to set email alerts
|

First Experiences with Over-the-Counter Hearing Aids for Mild-to-Moderate Hearing Loss: A Case Report

Lucas A. Berenbrok,
Annie Duchen,
Tony Cyr
et al.

Abstract: This patient case report describes a first experience in late 2022 and early 2023 with over-the-counter (OTC) hearing aids for a 71-year-old male with self-perceived, age-related hearing loss. The patient reported no “red flag” medical conditions that would preclude him from safely using an OTC hearing aid device. After also meeting inclusionary criteria required to be printed on the device label, the patient was offered FDA registered OTC hearing aids. The first device pair was returned due to malfunction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Midey and colleagues revealed that 94% of 85 pharmacists who responded to an online survey expressed interest in increasing their knowledge of OTC HAs, 72% expressed interest in selling OTC HAs in their pharmacies, and 73% expressed interest in assisting patients with the selection of OTC HAs [ 12 ]. Evidence also has suggested that pharmacists were capable of successfully providing OTC HAs to their patients [ 15 ]. In this study, a pharmacist, working in collaboration with an audiologist, confirmed the degree of hearing loss, ensured that contraindications for HA use were not present, assessed the patient’s perceived difficulty with their hearing loss, and helped with the setting of the initial HAs as well as a second set of aids after a malfunction of the first set.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Midey and colleagues revealed that 94% of 85 pharmacists who responded to an online survey expressed interest in increasing their knowledge of OTC HAs, 72% expressed interest in selling OTC HAs in their pharmacies, and 73% expressed interest in assisting patients with the selection of OTC HAs [ 12 ]. Evidence also has suggested that pharmacists were capable of successfully providing OTC HAs to their patients [ 15 ]. In this study, a pharmacist, working in collaboration with an audiologist, confirmed the degree of hearing loss, ensured that contraindications for HA use were not present, assessed the patient’s perceived difficulty with their hearing loss, and helped with the setting of the initial HAs as well as a second set of aids after a malfunction of the first set.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Berenbrok, Mormer, and colleagues have reported on collaborations in their recent work [ 11 , 12 , 13 , 14 , 15 ]. These researchers, representing pharmacy and audiology professions, have developed 26 competency statements for pharmacists when providing hearing healthcare in pharmacies [ 14 ], developed online training sessions designed to help pharmacists become familiar with supporting adults with hearing loss [ 13 ], and reported findings from a patient who received support from a pharmacist in the provision of OTC HAs [ 15 ]. Evidence has also indicated that pharmacists are very interested in working with audiologists to support adults with hearing loss [ 11 , 12 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation